Death by a thousand cuts - Brook, Timothy (Harvard University Press, 2008)
The execution of Wang Weiqin -- The laws of punishment in late-imperial China -- The origins and legitimacy problems of lingchi -- Lingchi in the Ming Dynasty -- Tormenting the dead -- Chinese torture in the Western mind -- Qing executions and European supplices -- Georges Bataille and the supplicié chinois -- Retrospective